Novel Somatostatin Receptor Ligands Therapies for Acromegaly - Paragliola, Rosa Maria; Salvatori, Roberto (Frontiers in Endocrinology, 2018)
Surgery is considered the treatment of choice in acromegaly, but patients with persistent disease after surgery or in whom surgery cannot be considered require medical therapy. Somatostatin receptor ligands (SRLs) octreotide, lanreotide and the more recently approved pasireotide, characterized by a broader receptor ligand binding profile, are considered the mainstay in the medical management of acromegaly. However, in the attempt to offer a more efficacious and better tolerated medical approach, recent research has been aimed to override some limitations related to the use of currently approved drugs, and novel SRLs therapies, with potential attractive features, have been proposed. These include both new formulation of older molecules and new molecules. Novel octreotide formulations are aimed in particular to improve patients’ compliance and to reduce injection discomfort. They include an investigational ready-to-use subcutaneous depot octreotide formulation (CAM2029), delivered via prefilled syringes, and oral octreotide, that uses a “transient permeability enhancer” technology, which allows for octreotide oral absorption. Another new delivery system is a long-lasting octreotide implant (VP-003), which provide stable doses of octreotide throughout a period of several months. Finally, a new SRL DG3173 (somatoprim), seems to be more selective for GH secretion, suggesting possible advantages in the presence of hyperglycemia or diabetes. How much these innovations will actually be beneficial to acromegaly patients in real clinical practice remains to be seen.